Strategic performance measurement system design and organisational capabilities / Rapiah Mohamed, Wee Shu Hui, Ibrahim Kamal Abdul Rahman and Rozainun Abdul Aziz - Mohamed, Rapiah; Hui, Wee Shu; Abdul Rahman, Ibrahim Kamal; Abdul Aziz, Rozainun (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2009)
This paper reports the results of strategic performance measurement system (SPMS) design and organisational capabilities i.e. market orientation, entrepreneurship, innovation and organisational learning. The main research question of this study is ‘does the adoption of SPMS that consists of financial and non-financial measures enhance organisational capabilities’. The data was collected using a mail survey to top management of listed companies in Malaysia. The results found that overall SPMS design had a statistically significant influence on organisational capabilities.